Transformative Choice, Practical Reasons and Trust. Issue 2 (15th March 2018) - Compaijen, Rob
Abstract: In this article I reflect on the question of whether we can have reason to make transformative choices. In attempting to answer it, I do three things. First, I bring forward an internalist account of practical reasons which entails the idea that agents should deliberate to the best of their ability. Second, I discuss L.A. Paul's views on transformative choice, arguing that, although they present a real problem, the problem is not as profound as she believes it is. Third, I argue that, given the situation in which we face transformative choices (a situation of principled uncertainty though not cluelessness), trust is an appropriate response to transformative choices, and that when one's trust that one's current desires will be fulfilled in making a transformative choice is reasonable, one has a reason to make it. Thus, trust turns out to be a crucial response to a profound problem each of us will face during our lives.